Does School Violence occur in pre-school and primary education? A proposal for assessment and management. - Albaladejo-Blázquez, Natalia; Ferrer-Cascales, Rosario; Reig-Ferrer, Abilio; Fernández-Pascual, MªDolores (Anales de Psicología / Annals of Psychology, 2013)
Traditional research on school violence has focused mainly on the later primary education grades and on secondary education, and has barely addressed the presence, characteristics, assessment, and intervention of interpersonal problems at early ages. The aim of this study was to construct and validate a questionnaire that identifies the onset and the most frequent forms of school violence in the first years of schooling in order to design effective prevention programs. The study participants were 195 children from the last year of pre-school and the first stage of primary education. The research carried out demonstrates that the instrument, the Questionnaire for the Assessment of School Violence in the Pre-School and Primary School (Cuestionario de Evaluación de Violencia Escolar en Infantil y Primaria, CEVEIP), has adequate psychometric properties. The instrument includes 27 self-report items that assess seven typologies of violence that occur in the school setting at early ages from three perspectives: observed violence, experienced violence, and perpetrated violence. The results reveal that violent behavior of a low or moderate frequency and intensity is present from the first years of schooling. These levels of violence could be better managed in the educational setting in order to enhance students´ personal development.